FOUR WHEELS DRIVE TRACTOR PERFORMANCE WITH DESIGNED PLOW (EXPERIMENTAL MODEL) AND LOCAL MADE (113) AND ITS EFFECT IN POWER REQUIREMENTS AND PLOWING CRITERIA - Yassen H. Al-Tahan (Mesopotamia Journal of Agriculture)
Field experiment was conducted to study the performance of the four wheels drive tractor with two plow types [new designed (experimental model) and local made (113)], two levels of the depths 20-25 and 25-30 cm and three different speeds 4.4 and 6 and 9 km/hr. Then their effects in power requirements criteria (drawbar power, slippage percentage and effective field capacity). And plowing criteria (soil inversion percentage, vertical stability, sidelong stability). In power requirements criteria, the designed mould board plow significantly surpassed and showed better results in effective field capacity, while the different levels of depths and speeds had significant effects in all power requirements criteria. All interactions (plows and depths, plows and speeds, depths and speeds) had significant effects in all power requirements criteria. In plowing quality characteristics, the designed plow surpassed and showed better results.